Moisture sorption isotherm and changes in physico-mechanical properties of films produced from waste flour and their application on preservation quality of fresh strawberry - Rattana Muangrat (2018)
© 2018 The Authors. Food Science & Nutrition published by Wiley Periodicals, Inc. Waste flour from the noodle industry was used to produce films, which were plasticized with 40% w/w glycerol:sorbitol at 2:1, 3:1, and 4:1 w/w and formulated with 200 ppm potassium sorbate. Henderson's equation was found to be the best estimator for moisture sorption isotherm of the films stored at 5, 25, and 45°C, and then, equilibrated at 0.11, 0.23, 0.32, 0.43, 0.58, 0.64, 0.76, 0.84, and 0.93 water activity. Developed flour films (plasticized with 2:1 w/w glycerol:sorbitol/formulated with 20% w/w potassium sorbate), with the best mechanical properties (tensile strength of 1.05 MPa; elongation at break of 73.01%), were used to cover fresh strawberries on a polystyrene foam tray. It was found that higher average phenolic contents, antioxidant activity, and firmness were found in strawberries wrapped in plasticized/formulated films, when compared against both films without potassium sorbate and without film (control). Furthermore, a lower average total microorganism count was found for fresh strawberries wrapped in the plasticized/formulated films, when compared with films without potassium sorbate.